Dinosaur chase! - Blathwayt, Benedict (London : Random House, 2006)
Fin is bullied for being different from the other dinosaurs until one day he does something that amazes them.
Includes CD.
1.6
K-3
Keywords: Bullies -- Fiction; Dinosaurs -- Fiction; Bullies -- Fiction; Dinosaurs -- Fiction